Approaching sources in their contexts
1 online resource.
Keywords: "In this book, twelve academics examine how space, time and performance interact to co-create context for source analysis. Supported by a range of case studies that cover 2000 years and stretch across the Americas and Europe, the contributors embed lessons and methodological approaches that can be adapted and adopted by those working with similar sources, offering students both a theoretical and practical demonstration of how to analyse sources within their contexts. Drawing out common threads to help with the reader's own historical investigation, this book encourages a broad and inclusive approach to the physical and social contexts of historical evidence"--